Foot and lower extremity anatomy to color and study - Poritsky, Ray (Hanley & Belfus, 2001)
This book is disigned to help students learn the complex anatomy of the lower extremity. It also serves as a comprehensive review for students at the competion of their gross anatomy couse. The various muscles, nerves and blood vessels of the lower limb are depicted in bold black and white drawings for the reader to label and color.